Memorializing the Middle Classes in Medieval and Renaissance Europe - Leader, Anne (Book collections on Project MUSE., 2018)
This study investigates commemorative practices in Cyprus, Flanders, France, Germany, Italy, Poland, and Spain between the twelfth and seventeenth centuries. Offering a broad overview of memorialization practices across Europe and the Mediterranean, individual chapters examine local customs through particular case studies. These essays explore complementary themes through the lens of commemorative art, including social status; personal and corporate identities; the intersections of mercantile, intellectual, and religious attitudes; upward (and downward) mobility; and the cross-cultural exchange of memorialization strategies.--Publisher description.